Applying Psychology to Study Creativity: Shown Through Painting Exhibition: Rejecting Old Through Art - Mudafiatun Isriyah; Zada Wildaningrum Mustika Ratri (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2022)
This study aims to determine what is in the creator's creation: motives, impulses, thought processes and influences that direct painters to realize creativity. This study uses a qualitative descriptive research method. The source of data in this research is in the form of the painting exhibition 'Menolak Tua through Karya'. The data in this study is that the anatomy of creativity has been studied by several leading psychologists, among others: the pursuit to provide a more empirical basis in the visual arts. The steps for collecting data and the research process were carried out as follows: (1) describing all of the paintings on display; (2) identify the work; (3) codifying data; (4) the data is analyzed applying psychology to apply creativity which includes innovation and creativity, intelligence and creativity, motivation and creativity; (5) conclude the research results. The results of this study show that in this painting exhibition there is a psychological application in creativity.